HAK RUANG ZONA EKONOMI EKSKLUSIF INDONESIA DI LAUT NATUNA UTARA DARI SUDUT PANDANG UNCLOS III (1973-1982) DALAM PENYELESAIAN TUMPANG TINDIH BATAS LAUT - Eka Djunarsjah; Briantara Revidinda Putra; Dwi Wisayantono (Kokoh, 2023)
The issue of the North Natuna Sea between Indonesia and China has become a crucial issue that has yet to find a bright spot to resolve disputes in the region. The claim of the nine dash line or nine dashes unilaterally by China has caused losses for Indonesia to the full sovereignty and integrity of the country which is included in the Exclusive Economic Zone in the North Natuna Sea. Although each country has ratified UNCLOS (United Nations Convention of the Law of the Sea) or ratified it as the International Law of the Sea, it means that every decision is based on the force of law that has been mutually agreed upon. China considers claims based on historical aspects (historical) at the time of their ancestors in the past. However, according to Law Number 5 of 1983 referring to UNCLOS, it is stated that the Indonesian Exclusive Economic Zone (ZEEI) is a path outside and bordering the Indonesian Territorial Sea as determined based on the applicable law concerning Indonesian Waters which includes the seabed, the land beneath it. , and the water above it with an outer limit of 200 nautical miles measured from the baseline so that the North Natuna Sea is or is included in the full rights of Indonesia. In this case, Indonesia has binding legal force to file a claim against or defense against China which claims arbitrarily and clearly violates the International Law of the Sea (UNCLOS). Through the writing of this paper, it aims to analyze and deliver input from the scientific aspects of geodesy and geomatics through an opinion on the resolution of the North Natuna Sea problem that Indonesia has strong evidence and is in accordance with the law so as to provide opportunities for resolving disputes in the region.Keywords:Â Exclusive Economic Zone,Dispute, North Natuna Sea, Nine Dash Line, UNCLOS